2020
DOI: 10.1038/s41389-020-0218-z
|View full text |Cite
|
Sign up to set email alerts
|

BET protein inhibitor JQ1 downregulates chromatin accessibility and suppresses metastasis of gastric cancer via inactivating RUNX2/NID1 signaling

Abstract: Chromatin accessibility is critical for tumor development, whose mechanisms remain unclear. As a crucial regulator for chromatin remodeling, BRD4 promotes tumor progression by regulating multiple genes. As a small-molecule inhibitor of BRD4, JQ1 has potent chemotherapeutic activity against various human cancers. However, whether JQ1 has potential anti-tumor effects and how JQ1 regulates global transcription in gastric cancer (GC) remain largely unknown. In this research, we found BRD4 was highly expressed in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…Consistent with our previous findings, BET inhibitors could suppress melanoma proliferation in vitro (Figure 5 D) . BET inhibitors have been reported to have different roles in tumor migration and invasion in different cancers types 31 - 34 . To explore the role of BET inhibitors in melanoma migration and invasion, we performed wound healing and Transwell assays, and results showed delayed wound repair and a smaller number of invasive cells after BET inhibitors treatment (Figure 5 E-G) .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our previous findings, BET inhibitors could suppress melanoma proliferation in vitro (Figure 5 D) . BET inhibitors have been reported to have different roles in tumor migration and invasion in different cancers types 31 - 34 . To explore the role of BET inhibitors in melanoma migration and invasion, we performed wound healing and Transwell assays, and results showed delayed wound repair and a smaller number of invasive cells after BET inhibitors treatment (Figure 5 E-G) .…”
Section: Resultsmentioning
confidence: 99%
“…Third, ATACseq can be used to predict the risk of tumor metastasis by detecting metastasis-related open chromatin (24). Finally, ATACseq can be used to explore the target of cancer treatment by studying drugs as inhibitors of transcription factors (25). The highest number of articles that used ATAC-seq was found for the mechanism of cancer, with 51 articles (Figure 3A).…”
Section: Characteristics Of Atac-seq-related Articles In Cancer Biologymentioning
confidence: 99%
“…ATAC-seq has applications in the pathogenesis (26), targeted therapy (27), and immunotherapy (28) of leukemia. The type of cancer with the second highest number of included articles that used ATAC-seq was digestive system tumors at 14 articles, including gastric cancer (25), pancreatic cancer (29), liver cancer (30), and colorectal cancer (31). Of the included articles, 6, 3, and 2 were on breast cancer, ovarian cancer, and sarcoma, respectively.…”
Section: Characteristics Of Atac-seq-related Articles In Cancer Biologymentioning
confidence: 99%
“…Reported studies have already indicated that NID1 was an indicator of prognosis in several tumors [42]. The downregulated NID1 could improve cancer patients' survival outcomes by deactivating the MET, which may prohibit the migration and invasion of cancer cells [44]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 94%